2019
DOI: 10.3390/ani10010057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Vegetable Oils on Mammary Lipid-Related Genes in Holstein Dairy Cows

Abstract: This study analyzed effects of vegetable oils fed to dairy cows on abundance of genes related to lipid metabolism in milk somatic cells (MSC). During 63 days, 15 cows were allocated to 3 treatments: a control diet with no added lipid the same diet supplemented with olive oil (OO, 30 g/kg DM) or hydrogenated vegetable oil (HVO, 30 g/kg DM). On days 21, 42 and 63, MSC were obtained from all cows. Relative abundance of genes involved in lipid metabolism in MSC from cows fed control on days 42 and 63 was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 36 publications
2
15
1
Order By: Relevance
“…This enzyme is regulated by various factors associated with glucose content of the cell, glucose:glucagon ratio, and blood thyroxine concentration 18,19 . Our results differ from studies where relative expression of ACACA was not affected when cows were fed olive oil 6 and soybean oil 20 and when goats were supplemented with soybean 21 . The reduction in ACACA regulation caused by SO and FO could be related to an increase in dietary PUFA supply, which is normally related to downregulation of transcription regulatory genes such as SREBF1.…”
Section: Effects Of So and Fo On Lipid Metabolism-related Genes In Mscontrasting
confidence: 99%
See 4 more Smart Citations
“…This enzyme is regulated by various factors associated with glucose content of the cell, glucose:glucagon ratio, and blood thyroxine concentration 18,19 . Our results differ from studies where relative expression of ACACA was not affected when cows were fed olive oil 6 and soybean oil 20 and when goats were supplemented with soybean 21 . The reduction in ACACA regulation caused by SO and FO could be related to an increase in dietary PUFA supply, which is normally related to downregulation of transcription regulatory genes such as SREBF1.…”
Section: Effects Of So and Fo On Lipid Metabolism-related Genes In Mscontrasting
confidence: 99%
“…When cows are fed dietary oils, different responses take place at molecular levels, such as changes in expression of genes related to lipid metabolism at adipose tissue 3 , 4 or at mammary gland 5 7 levels. In this regard, we have observed that degree of FA saturation can trigger differential effects in expression of lipid-related genes in the mammary gland 6 . In fact, those alterations were observed in different biological functions, such as FA synthesis ( ACACA ), acetate and FA activation and intra-cellular transport ( FABP3 , FABP4 ), lipid droplet formation ( PLIN2 ), and transcription regulation ( THRSP ), and this was observed over a period of 63 days of lipid supplementation with either palm oil (as a saturated FA source) or olive oil (as an unsaturated FA source).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations